The Study of Time Spent on Nursing Activities in Anesthesia Unit, Phrae Hospital - Dumkoengtham , Supang; Nantsupawat , Apiradee; Thungjaroenkul , Petsunee (Nursing Journal CMU, 2020)
The study of time spent on nursing activities indicates the workload which is important to nursing. The purposes of this descriptive study was to analyze nursing activities according to the needs of each type and to study the number of hours of nursing activities for each type of patient receiving anesthesia service. The sample consisted of 89 general anesthesia patients, selected by purposive sampling, 15 nurse anesthetists, 1 professional nurse working in a recovery room in the anesthetist unit Phrae Hospital. The study instruments were 1) Handbook of direct and indirect anesthetical nursing activities dictionary. The content accuracy index was 0.90 2) The record form to the amount of time that nurse anesthetists use to perform direct and indirect nursing activities of anesthetists. The observation consistency index was 0.92. Using the concept of human resource planning for nursing personnel of Srisatidnarakul (2007) and use patient classification with ASA Class. Gather data by observing and recording the time spent on performing nursing activities. Data were analyzed using descriptive statistics. The results show that This study found patients with type ASA I - ASA III and did not find patients with type ASA IV- ASA VI by direct nursing activities found 15 activities and indirect nursing activities found 16 activities. Total time spent in nursing activities in ASA I, ASA III, and ASA II patients, average 4.44, 4.04 and 4.03 hours respectively. The results of this study will be information for executives to use as a guideline in planning the appropriateness of nursing staffing.